Haemophilus ducreyi RpoE and CpxRA Appear To Play Distinct yet Complementary Roles in Regulation of Envelope-Related Functions - Gangaiah, Dharanesh (J Bacteriol, 2014)
Haemophilus ducreyi causes the sexually transmitted disease chancroid and a chronic limb ulceration syndrome in children. In humans, H. ducreyi is found in an abscess and overcomes a hostile environment to establish infection. To sense and respond to membrane stress, bacteria utilize two-component systems (TCSs) and extracytoplasmic function (ECF) sigma factors. We previously showed that activation of CpxRA, the only intact TCS in H. ducreyi, does not regulate homologues of envelope protein folding factors but does downregulate genes encoding envelope-localized proteins, including many virulence determinants. H. ducreyi also harbors a homologue of RpoE, which is the only ECF sigma factor in the organism. To potentially understand how H. ducreyi responds to membrane stress, here we defined RpoE-dependent genes using transcriptome sequencing (RNA-Seq). We identified 180 RpoE-dependent genes, of which 98% were upregulated; a major set of these genes encodes homologues of envelope maintenance and repair factors. We also identified and validated a putative RpoE promoter consensus sequence, which was enriched in the majority of RpoE-dependent targets. Comparison of RpoE-dependent genes to those controlled by CpxR showed that each transcription factor regulated a distinct set of genes. Given that RpoE activated a large number of genes encoding envelope maintenance and repair factors and that CpxRA represses genes encoding envelope-localized proteins, these data suggest that RpoE and CpxRA appear to play distinct yet complementary roles in regulating envelope homeostasis in H. ducreyi.